Gambaran Tingkat Pengetahuan Nelayan tentang Kesehatan dan Keselamatan Kerja - Andi Hendrawan; Aji Kusumastuti Hendrawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Akademi Maritim Nusantara Cilacap, 2020)
Fishermen's occupational health and safety is very important. Neglect of safety tends to increase economic and environmental costs such as decreased production, medical costs, pollution and inefficient energy use. The aim of this study was to describe the level of knowledge about fishermen's occupational health and safety. The study involved 40 fishermen in Jeruklegi Wetan Village, Jeruklegi District, Cilacap Regency. Conducted with a survey method by distributing questionnaires and interviews. Fishermen's occupational health and safety. Based on the research that most were in the poor category, namely 20 people or 50% and good and enough categories respectively, namely 10 people or 25%.